A Comprehensive Review of Wind Turbine Modeling for Addressing Energy Challenges in Nigeria and South Africa in the 4IR Context - Tolulope Babawurun; Daniel Raphael Ejike Ewim; Temiloluwa Olatunji Scott; Chukuneye Neye-Akogo (The Journal of Engineering and Exact Sciences)
Wind energy is a promising renewable energy source that can contribute to addressing the energy challenges faced by countries such as Nigeria and South Africa. Wind turbine modeling has emerged as a critical tool for optimizing the design, operation, and maintenance of wind turbines, as well as for integrating wind energy into the power grid. This approach can potentially enhance the performance and reliability of wind turbines, increase their energy production, and reduce their environmental impact. The review examines various wind turbine modeling approaches and techniques. It also discusses these modeling approaches' strengths and limitations and highlights their potential applications in addressing energy challenges in Nigeria and South Africa. Overall, this comprehensive review provides valuable insights into the potential for wind turbine modeling to address energy challenges in Nigeria and South Africa. It provided a thorough analysis of the current state of wind turbine modeling technology and highlighted areas for further research and development.